The structure of madrasa education in nigeria and government initiatives - Busari Afeez Babatunde; Sarkanto; Eka Mahargiani Rokhma; Mubayinah; Triana Hermawati (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This research discusses the role and dynamics of madrassas in Nigeria, starting from the background of the development of Islamic educational institutions rooted in local traditions and historical influences of the Sokoto Caliphate, to reveal the structure, types, curriculum, and challenges faced by traditional and modern madrassas in the North and South. This study aims to determine the structure in madrasas in the country and government initiatives in madrasas. Qualitative methods are used through interviews and field observations, combined with analyzing library documents and sources. The results of the study show that there are significant differences between madrassas in the North that emphasize Islamic and community-based education, and madrassas in the South that prioritize integrated education between religion and the public, as well as obstacles such as limited resources, inequality of facilities, and modernization demands. Strengthening governance, curriculum integration, and government support are key to optimizing madrasas as relevant educational and social institutions in Nigeria.